A Combined High-, Medium-, and Low-Voltage Test System for Stability Studies with DERs - Escobar, Francisco; García, Jorge; Víquez, Juan M.; Valverde, Gustavo; Aristidou, Petros (My University, 2020)
Future scenarios with high penetration of Distributed Energy Resources (DERs) call out for detailed network modelling at all voltage levels. The challenges of building a network model that is realistic at both the transmission and distribution levels have led to test systems that use aggregate medium-voltage (MV) loads. In this paper, we present a methodology that uses low-voltage networks with a sensible load allocation to disaggregate MV loads that were previously used in combined Transmission-Distribution (TD) network simulations. The resulting network accurately captures the interaction of transmission and distribution networks, thereby proving useful for new control schemes and stability studies that account for the participation of small and large-scale distributed energy resources. This extended network model is a convenient tool for research, training, and teaching.
Keywords: Distributed energy resources; Modelling; Power system dynamics; Simulation; Synthetic network; Test system